Virtual Reality-assisted Smart Teaching Model to Enhance Climate Literacy and Participation In Climate Change Mitigation And Adaptation Of Secondary School Students' - S. Tabbu, Muhammad Ansarullah; Erman Syarif; Asham Bin Jamaluddin (Jurusan Teknik Informatika dan Komputer, 2024)
This study assesses the impact of a Virtual Reality-assisted Smart Teaching Model (VRSTM) on improving climate literacy and fostering active engagement in climate change mitigation and adaptation among secondary school students. A quasi-experimental design was used to compare the effectiveness of VRSTM with a Smart Teaching (ST) model and traditional teaching methods among eleventh graders at SMA Negeri 13 Makassar. Post-intervention data were analyzed using Analysis of Covariance (ANCOVA), which highlighted significant enhancements in climate literacy and student participation levels across the three groups. The findings reveal that students instructed through VRSTM scored higher in climate literacy (84.88) and in participation in climate change mitigation and adaptation activities (85.53) than those in the ST model (83.09 and 84.97, respectively) and the traditional teaching groups (78.72 and 79.84, respectively). These results demonstrate that integrating VR technology into educational models markedly improves students' comprehension of climate change and their commitment to implementing mitigation and adaptation measures. The research highlights the potential of VR technology in creating more effective learning environments for tackling global challenges such as climate change, contributing valuable insights to the fields of educational technology and environmental education. It underscores the efficacy of VR-assisted learning models in boosting student engagement and involvement in addressing significant environmental concerns.